DEVELOPMENT OF METHODS AND ALGORITHMS TO BUILD ASPEAKER VERIFICATION IN KAZAKH LANGUAGE - Rashid, Sh.; Kuanyshbay, D.; Nurkey, A. (Journal of Emerging Technologies and Computing, 2024)
Speaker verification interfaces are gaining more and more popularity in both academic and commercial industries. It's connected with the latest advances in this area, which can be seen firsthand in our daily life: voice interfaces in computers, robots, cell phones, Internet browsers, and even household appliances. The relevance of the development of Kazakh speech recognition systems arises in connection with the growing needs in the field ofpublic services, provided within the framework of electronic government (egov). Availability voice interfaces will open access to government services for people with disabilities, as well as people living in remote regions and havingthe only way of access in the form of telephones.